A Deal that Does Not Die: The United States and the Rise, Fall and Future of the (CP)TPP1. (27th August 2019) - Ji, Xianbai; Rana, Pradumna B.
Abstract : The Trans‐Pacific Partnership (TPP) is one of the most politically resilient economic arrangements of the past decades. Its evolution, including the highs and lows, is closely tied to the shifting positions of the United States. This article examines the role played by the United States in the rise, fall and future of the TPP and its successor, the Comprehensive and Progressive Agreement for TPP (CPTPP). First, this article revisits Washington's threefold geo‐economic interest behind the original TPP in terms of projecting influence in Asian affairs, supporting Obama's Rebalance to Asia strategy, and leading the regional rule‐writing efforts to facilitate 21st century trade and investment. Second, this article delves into offering an explanation of the loss of the TPP in the United States. It argues that the TPP was crippled under an overlay of bad timing, bad politics and bad context. Specifically, the 2016 elections, Trump's disapproving views on the TPP, and the narrow and underperforming US trade policy ecosystem at large were the key factors leading to the US withdrawal from the TPP. In conclusion, the article considers the future of the CPTPP by asking and answering three questions: Will China and other countries join the bloc? Will the CPTPP evolve into a Free Trade Area of the Asia‐Pacific? And, are the CPTPP and the China‐backed Regional Comprehensive Economic Partnership part of the Asia‐Pacific's constructive response to Trump's protectionism?